Projeto, fabricação e caracterização de al2o3- zro2-sicw em gradação funcional com wc-co - Fraga, Luma Gonçalves (2023)
Machining is a manufacturing process which aims to give shape or finishing to parts by removing material. For this purpose, cutting tools are used, and they need to have high hardness, high wear resistance, chemical inertness, and fracture toughness. The cemented carbide (WC-Co) has a good combination of hardness and fracture toughness; however, they lose properties at elevated temperatures. The alumina (Al2O3) based ceramic cutting tools have high hardness, wear resistance, and chemical stability, even at great temperatures, however present low fracture toughness. Owing to the difficulty of grouping the properties in one engineering material, Functionally Graded Materials (FGM) have arisen as an alternative. Those have two or more phases varying in relation to each other, creating an intentional gradient of properties throughout the material. This work aims to design, manufacture, and characterize a heterogeneous composite of eight layers of Al2O3- ZrO2-SiCw in gradation with WC-Co, and evaluate its properties in comparison with the homogeneous composites Al2O3-ZrO2-SiCw and WC-Co. To design the FGM, a one-dimensional thermomechanical model was used to predict the residual stress. The sintering was made by pulsed electric current (PECS) in medium vacuum atmosphere, with the axial pressure of 50 MPa, dwell temperature of 1500°C for the Al2O3-ZrO2-SiCw, 1250°C for the WC-Co, and 1450°C for the FGM. In order to characterize the physical properties, the experimental density was evaluated using Archimedes’ principle and the thermal conductivity measured. DRX, MEV and EDS analyses were carried out to characterize the elements and phases of the powders and sintered. Scratch hardness, Vickers hardness and indentation fracture toughness tests were performed to characterize the mechanical properties of the sintered. The prediction of the residual stress showed a traction tension of 508 MPa in the first layer, composed only by Al2O3-ZrO2-SiCw. However, this tension is below the rupture strength limit of the material, such that no cracks were observed after the sintering. The samples, in general, showed up high densification, highlight to the FGM that achieve the relative density of 98.61%. The thermal conductivity of the FGM increased 46% when compared to the ceramic composite, due to the addition of WCCo. It was observed the variation of the scratch hardness over the gradient and the increase of 115% in the friction coefficient between the first and the last layer. The Vickers hardness in the first layer was of 1390.55 HV, while in the last was 1279.73 HV, showing a variation of 8%. An increase around of 36% in the fracture toughness occurred along the layers of the FGM. All the results showed a variation of properties of the FGM over the layers and regarding the homogeneous materials. They also indicate the viability of manufacturing FGM cutting tools, with cutting edge in the first layer. However, to validate its use, machining tests are needed.